Toward Disentangling the Multiple Nutritional Constraints Imposed by Planktothrix: The Significance of Harmful Secondary Metabolites and Sterol Limitation - Schwarzenberger, Anke; Kurmayer, Rainer; Martin-Creuzburg, Dominik (Frontiers in Microbiology, 2020)
The harmful bloom-forming cyanobacterium Planktothrix is commonly considered to be nutritionally inadequate for zooplankton grazers, resulting in limited top-down control. However, interactions between Planktothrix and zooplankton grazers are poorly understood. The food quality of Planktothrix is potentially constrained by morphological properties (i.e. filament formation), the production of harmful secondary metabolites, and a deficiency in essential lipids (i.e. primarily sterols). Here, we investigated the relative significance of toxin production (microcystins, carboxypeptidase A inhibitors, protease inhibitors) and sterol limitation for the performance of Daphnia feeding on one Planktothrix rubescens and one P. agardhii wild-type/microcystin knock-out mutant pair. Our data suggest that the poor food quality of both Planktothrix spp. is due to deleterious effects mediated by various harmful secondary metabolites and that the impact of sterol limitation is partially or completely superimposed by toxicity. The significance of the different factors seems to depend on the metabolite profile of the considered Planktothrix strain and the Daphnia clone that is used for the experiments. The toxin-responsive gene expression (transporter genes, gpx and trypsin) and enzyme activity patterns revealed strain-specific food quality constraints and that Daphnia is capable of modulating its physiological responses according to the ingested Planktothrix strain. Future studies need to consider that Planktothrix–grazer interactions are simultaneously modulated by multiple factors to improve our understanding of top-down influences on Planktothrix bloom formation.